MENGATASI KESULITAN BELAJAR BAHASA INDONESIA PADA PESERTA DIDIK KELAS VIII-I DI SMP NEGERI 3 KEPANJEN - prily salma salma; Hari Suryono; Purwati Anggraini; Hari Windu Asrini (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Students who experience difficulties in learning must be immediately handled with guidance so that a conducive situation can be realized in the teaching and learning process. This study aims to 1) identify the problems faced by the case subjects, 2) efforts to deal with the learning difficulties of the case subjects. The method used in this study is a descriptive qualitative approach, in the form of field research. On observation during face-to-face teaching and learning in class VIII starting on October 2, 2021 until March 12, 2022. Data collection with documentation and interviews was carried out one day on June 26, 2022 in class VIII-I. The results of the research based on data, students were diagnosed with learning difficulties as evidenced by the difficulty of concentrating on understanding the lesson, often paying attention to the teacher with a blank look, often daydreaming, tending to be passive, and students often found sleeping in class. In connection with this, a prognosis is carried out as evidenced by the findings that learning difficulties are due to causative factors. If it is not addressed immediately, it is likely that it will be difficult to control lazy learning behavior which increasingly makes learning achievement decline, frequent truancy, late for class, destructive attitude, and the subject of the case can be triggered by a negative attitude that initially gets a score from school until retirement. themselves or are expelled from school. For this reason, the handling of tutoring is carried out, providing additional assignments at home which are immediately handled individually. In addition, giving advice on the subject of the case if there is a problem, you can tell the homeroom teacher, counseling guidance teacher, or a trusted friend. From the results of this study it can be concluded that the problems in the case studies have been handled by researchers, homeroom teachers, and counseling teachers. The role of parents is very helpful in providing guidance to students, so as to improve student achievement in classroom learning.